Indirect comparisons of siponimod with fingolimod and ofatumumab in multiple sclerosis: assessing the feasibility of propensity score matching analyses. (2nd November 2021) - Samjoo, Imtiaz A.; Worthington, Evelyn; Haltner, Anja; Spin, Paul; Drudge, Christopher; Cameron, Chris; Brennan, Róisín; Dahlke, Frank; Adlard, Nicholas
Abstract: Objective: Head-to-head trials comparing siponimod with fingolimod or ofatumumab in patients with multiple sclerosis (MS) are lacking. Instead, the comparative efficacy of siponimod can be derived from indirect treatment comparisons (ITCs). We assessed the suitability of ITCs leveraging individual patient data from relevant phase III trials across different MS phenotypes. Methods: One siponimod trial in patients with secondary progressive MS (SPMS), four fingolimod trials (three in relapsing-remitting MS [RRMS], and one in primary progressive MS [PPMS]), and two ofatumumab trials in relapsing MS (RMS) were considered. The suitability of ITCs was evaluated based on trial design, patient eligibility criteria, baseline patient characteristics, placebo response, and outcome definitions for each trial. Analyses deemed feasible were conducted using one-to-one propensity score matching (PSM). Results: An ITC between siponimod in SPMS and either fingolimod in RRMS or ofatumumab in RMS was not feasible because of insufficient overlap in key patient characteristics (e.g. disability level and relapse history) and differences in placebo response. However, a comparison between siponimod in SPMS and fingolimod in PPMS was feasible because of sufficient overlap in eligibility criteria and baseline characteristics. One-to-one PSM demonstrated siponimod was favored relative to fingolimod for time to 6- and 3-month confirmed disability progression though not significantly different (hazard ratio 0.76 [95% confidence interval 0.48–1.20; p -value = .240] and hazard ratio 0.80 [95% confidence interval 0.52–1.22; p -value = .300], respectively). Conclusions: For trials in MS, clinical phenotype is an important determinant of ITC feasibility. An ITC between siponimod in SPMS and either fingolimod in RRMS or ofatumumab in RMS was not feasible. The only feasible comparison was between siponimod in SPMS and fingolimod in PPMS.